New media: A new medium in escalating crises? - SIAH, Joanna Ann Mei (Institutional Knowledge at Singapore Management University, 2010)
Purpose– The use of new media in crisis is a double‐edged sword. On one hand, its pivotal role in online monitoring and dissemination of information can help an organisation manage crisis. On the other hand, it can also create organisational crisis. The purpose of this paper is to examine how new media can be used to escalate crisis.Design/methodology/approach– Four crises were examined: the 2008 Edison Chen sex scandal in Hong Kong; and in the USA, New York Taco Bell‐KFC rats infestation crisis in 2007; JetBlue Airways crisis in 2007, and the Kryptonite locks crisis in 2004.Findings– The very characteristics that make new media unique, such as user interactivity and integration of multimedia effects, are also its Achilles heel.Research limitations/implications– Research has revolved around new media as a tool, a useful aid in times of need. The paper presents an emerging and under‐explored side of new media of how it is used as an accessory in escalating crises.Practical implications– Practitioners can be equipped to better prepare themselves against the threats posed by new media.Originality/value– The paper has developed a new model on how organisations could harness new media to their advantage while implementing safeguards against possible threats posed by the medium. This model, called the new media crisis communication model, is an integration of the crisis management model posited by Gonzelez‐Herrero and Smith and the contingency theory of strategic conflict management.